2002
DOI: 10.1063/1.1483877
|View full text |Cite
|
Sign up to set email alerts
|

Effects of subgrid-scale modeling on time correlations in large eddy simulation

Abstract: The effects of the unresolved subgrid-scale ͑SGS͒ motions on the energy balance of the resolved scales in large eddy simulation ͑LES͒ have been investigated actively because modeling the energy transfer between the resolved and unresolved scales is crucial to constructing accurate SGS models. But the subgrid scales not only modify the energy balance, they also contribute to temporal decorrelation of the resolved scales. The importance of this effect in applications including the predictability problem and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
64
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 28 publications
12
64
1
4
Order By: Relevance
“…This is consistent with the previous observations in isotropic turbulence [6,7,13] and turbulent channel flows [20,21]. Moreover, the discrepancies between DNS and LES are larger in the convection direction than those in other two directions, especially in the viscous wall region.…”
Section: Space-time Correlation In Turbulent Channel Flowssupporting
confidence: 82%
See 3 more Smart Citations
“…This is consistent with the previous observations in isotropic turbulence [6,7,13] and turbulent channel flows [20,21]. Moreover, the discrepancies between DNS and LES are larger in the convection direction than those in other two directions, especially in the viscous wall region.…”
Section: Space-time Correlation In Turbulent Channel Flowssupporting
confidence: 82%
“…Previous work on isotropic turbulence has found that LES with an eddy-viscosity SGS model could over-predict decorrelation time scales of space-time correlations and under-predict their magnitudes [6,7]. These results are supported by the sweeping hypothesis [7,12]: the spacetime correlations in isotropic turbulence are mainly determined by energy spectra.…”
supporting
confidence: 75%
See 2 more Smart Citations
“…The way the small scales are treated in LES can affects our description of turbulence. Indeed, He et al (2002) have shown that LES results in a χ k (ω) that decreases at all resolved scales too rapidly with ω with respect to direct numerical simulations (DNS). Moreover, Jacoutot et al (2008b) found that computed mode excitation rates depend significantly on the adopted sub-grid model.…”
Section: Eddy Time-correlation χ K (ω)mentioning
confidence: 99%